2001
DOI: 10.1038/87004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular classification of head and neck squamous cell carcinoma using cDNA microarrays

Abstract: Head and neck squamous cell carcinoma (HNSCC) is the fifth most common cancer worldwide and accounts for 95% of the head and neck cancer cases in the Western world. Over the past three decades advancements in management have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 0 publications
5
82
1
1
Order By: Relevance
“…A direct comparison between that study and ours is difficult, because 1) the sample sizes were significantly different; 2) the sample processing procedures used in the two studies were significantly different; 3) the GeneChip analysis software and self-organizing maps algorithms used in that study to determine differential gene expression differed significantly from the regression-based algorithm used in our study; and 4) our statistical approach accounted for the potential false positive findings from making comparisons between a large number of genes in a small number of samples. Another study 52 -a retrospective analysis of 17 patients with head and neck carcinoma-identified 375 genes with expression that distinguished patients into two groups with distinct clinical outcomes. Given the prospective nature of our study, as we follow our patients for their disease outcome, we will be able to assess whether the 314 differentially expressed genes between OSCC tissues and normal tissues are the same genes that differentiate patients according to their disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A direct comparison between that study and ours is difficult, because 1) the sample sizes were significantly different; 2) the sample processing procedures used in the two studies were significantly different; 3) the GeneChip analysis software and self-organizing maps algorithms used in that study to determine differential gene expression differed significantly from the regression-based algorithm used in our study; and 4) our statistical approach accounted for the potential false positive findings from making comparisons between a large number of genes in a small number of samples. Another study 52 -a retrospective analysis of 17 patients with head and neck carcinoma-identified 375 genes with expression that distinguished patients into two groups with distinct clinical outcomes. Given the prospective nature of our study, as we follow our patients for their disease outcome, we will be able to assess whether the 314 differentially expressed genes between OSCC tissues and normal tissues are the same genes that differentiate patients according to their disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…To date, functional genomic analysis on HNSCC has been limited (126). Potential use of functional genomics with HNSCC may be in diagnosis, prognosis, and response to therapy.…”
Section: Functional Genomicsmentioning
confidence: 99%
“…HNSCC may be a useful system for studying lymphatic metastasis because of the high probability of lymphatic spread and low probability of hematogenous spread. A recent study has identified a gene signature for recurrent disease in HNSCC and several studies have investigated the changes in gene expression from normal tissue to carcinoma, but studies involving lymphatic metastasis have been limited by the small number of genes assessed and/or lack of a rigorous efficacy test of the metastatic signature (Alevizos et al, 2001;Belbin et al, 2002;Mendez et al, 2002;Hwang et al, 2003;Gonzalez et al, 2003;Leethanakul et al, 2003;Nagata et al, 2003;Chung et al, 2004;Ginos et al, 2004;Schmalbach et al, 2004;Warner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%